White Cord Syndrome and Acute Tetraplegia After Posterior Cervical Decompression: A Case Report. Issue 2 (April 2021) - Segal, Dale N.; Lunati, Matthew P.; Kukowski, Nathan R.; Michael, Keith W.
Abstract : Case: A 55-year-old man undergoes posterior cervical decompression and instrumentation for progressive cervical myelopathy and develops white cord syndrome (WCS) postoperatively with acute tetraplegia. Conclusion: WCS is a rare complication of spinal surgery that is thought to be due to reperfusion injury. We diagnosed WCS in our patient through postoperative examination consisting of acute tetraplegia and magnetic resonance imaging revealing increased signal in the cord. In this case, we used intravenous dexamethasone and mean arterial pressure above 90 mm Hg resulting in markedly improved clinical examination.